The Influence of Product Security on Purchasing Decisions with Hedonic Browsing as a Moderating Variable - Ida Harahap; Bangun Sentosa D. Haryanto; Nelly Patria; Marcelitha Tabita Montolalu; Eva Purnamasari (Yayasan Inovasi Kemajuan Intelektual, 2025)
This research is a quantitative study with an explanatory approach that uses previous research as the primary weapon for building, modifying, and proving the hypotheses developed by the researcher in this article. The data used in this study are primary data obtained by the researcher from two hundred and seventy-five Tokopedia consumers spread throughout Indonesia, with a minimum of two shopping categories. The data obtained by the researcher must be validated, the variables must be tested for reliability, and the hypothesis must be proven through the path coefficient. The flows mentioned by the researcher are a sequence of tests using the innovative PLS 4.0 analysis tool. The results of this article show that each hypothesis used in this study is acceptable and even more interesting than the three previous studies. The results from the first row of the third table above indicate that the Product Security variable can have a positive relationship and a significant influence on Purchasing Decisions. The P-values are positive and below the 0.05 significance level, namely 0.019. These results indicate that the higher the level of security of a product, the higher the level of comfort and consumer interest in making a Purchase Decision. The next row shows that the second hypothesis in this study is also acceptable because the P-values are positive and below the 0.05 significance level, namely 0.000. Thus, the higher the consumer's Hedonic Browsing nature, the stronger the influence of Product Security on Purchasing Decisions. Based on this, it can be concluded that the first and second hypotheses in this article can be accepted and proven.